A Survey of Load Balancing Algorithms in Cloud Environment - Tandel, J.M; Patel, HR (International Journal of Computer Sciences and Engineering, 2019)
Cloud computing provides storing and accessing of your data over the internet. Cloud computing delivers computing services (servers, databases, networking, software etc.) over the internet. There are various advantages of cloud computing including Virtual computing environment, On-demand services, Maximum resource utilization and easier use of services etc. Still, there are numerous issues in cloud computing related to Security, Resource provisioning, Server consolidation, and Virtual machine migration. Load Balancing is an essential task in the Cloud Computing environment to achieve maximum utilization of resources, minimize the response time and maximize the throughput of the overall system. Load balancing algorithms increase the efficiency of the system by equally distributing the workload among the completion process. In this paper, we have presented the performance analysis of various load balancing algorithms based on various dependent parameters by considering two main load balancing approaches: static and dynamic. The both types of the load balancing algorithm have some advantages as well as disadvantages. The main purpose is to analyze different algorithms based on the time factor.